Inklusivitas Masjid Sebagai Perekat Sosial: Studi Kasus pada Masjid Ash-Shiddiiqi Demangan Kidul Yogyakarta - Lukman Fajariyah (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2020)
In the history of Islamic civilization, the mosque is a center of worship and a place for social interaction. Based on this phenomenon, this paper tries to explore the role and function of the Ash-Shiddiiqi Mosque in social life. The social unity bound by the Ash-Shiddiiqi Mosque aims to strengthen the social relations of the community members in the Demangan Kidul neighborhood of Yogyakarta in order to realize an inclusive mosque. The method used in this study is a qualitative-descriptive method using the sociology approach of Emile Durkheim's theory of solidarity. This theory of solidarity becomes an analytical tool to reveal the role and function of the Ash-Shiddiiqi Mosque in an effort to strengthen individual relationships with other individuals in the Demangan Kidul Yogyakarta environment. The findings resulting from this research that; First, the Ash-Shiddiiqi Mosque is a place of worship that has a role and social social function such as the existence of a TPA (Taman Pendidikan Alquran) educational institution as a supporting facility in providing access to non-formal education to the community. Routine programs for pilgrims and the surrounding community are in the form of daily, weekly, monthly and yearly activities. Secondly, the inclusiveness of the Ash-Shiddiiqi Mosque in involving citizens in each of its programs which aims to strengthen social relations.